Teaching-learning methodology for the development of comprehensive reading in 3rd grade students - Rojas Colque, Hilber (2023)
The arrival of globalization has been characterized, without a doubt, by the growing invasion of technology and with it a greater demand at all levels of societies, groups and individuals, to which it is important to add the extrinsic need for certain skills that today they are essential in the development of any subject to remain competitive, not only at an individual level, but also in a collective sphere and one of those skills is knowing how to read comprehensively. It is in this direction that this article analyzes the real situation regarding the development of comprehensive reading of third grade students of the Educational Unit "Abraham Flores Velásquez" of the community of Alalay who showed limitations in understanding in the diagnosis section of different texts, where they present a spelled reading, that they can hardly understand what they read.